32.3.7.2 1-(Organochalcogeno)-2-(organooxy)alkenes (Update 2021) - Grimmer,J.; Krieg,S.-C.; Manolikakes,G. (Knowledge Updates 2021/1, 2021)
This is an update to the earlier Science of Synthesis contribution (Section 32.3.7) covering the synthesis and use of 1-(organochalcogeno)-2-(organooxy)alkenes. It focuses on the literature published in the period 2006 to 2019.
Keywords: Referencework; Science of Synthesis; alkenes; sulfur compounds; microwaves; radical vinylation; rearrangements; multicomponent reactions; ring-closing metathesis; dehydrogenation